Does Early Recruitment Predict Greater Physical Performance in Academy Soccer Players? - Maxime Hertzog; Darren J. Paul; George P. Nassis; Joao R. Silva (MDPI AG, 2018)
The purpose of this longitudinal study was to investigate whether recruitment status influences neuromuscular and endurance performances in academy soccer players over a 2-year training period (from Under-16 to Under-18). Thirty-seven male soccer players from an elite academy were selected and divided in two cohorts according to their recruitment status: Early Recruitment group (ER; n = 16), training and competing for the academy since Under-14 and Under-15 age groups, and; Late Recruitment group (LR; n = 21) included in the academy training process at Under-16. Squat (SJ) and countermovement jump with (CMJwA) and without arms swing (CMJ), 10-m sprint time, and Vam-Eval test (MAV) were performed in three successive occasions always pre-season (Under-16, Under-17 and Under-18 age groups, T1, T2, and T3 respectively). A two-way (recruitment status × time) analysis of variance with repeated measurements was performed as well as the magnitude of difference using both effect size and magnitude-based inferences. There was no difference between ER and LR for MAV, 10 m-sprint, and SJ from T1 to T3. However, LR players presented non-significant small and possibly greater improvement in CMJ (ES = 0.4) and CMJwA (ES = 0.4) than ER players at T2. These data indicate that early recruitment is not likely to result in greater physical performance improvement at the age of 18.